(untitled) (Journal of Oriental Studies, 2016)
In the article was carried out comparative analysis of word曰in Kazakh, Russian and English languages.The study conducted on translated novel «Miss Ying-Ning, or The laughing girl» of Chinese writer Pu Sunlin into the appropriate languages.